Lenalidomide Maintenance After Autologous Stem-Cell Transplantation in Newly Diagnosed Multiple Myeloma: A Meta-Analysis - McCarthy, Philip L; Holstein, Sarah A; Petrucci, Maria Teresa; Richardson, Paul G; Hulin, Cyrille; Tosi, Patrizia; Bringhen, Sara; Musto, Pellegrino; Anderson, Kenneth C; Caillot, Denis; Gay, Francesca; Moreau, Philippe; et al. (Journal of clinical oncology, 2017)
Purpose Lenalidomide maintenance therapy after autologous stem-cell transplantation (ASCT) demonstrated prolonged progression-free survival (PFS) versus placebo or observation in several randomized controlled trials (RCTs) of patients with newly diagnosed multiple myeloma (NDMM). All studies had PFS as the primary end point, and none were powered for overall survival (OS) as a primary end point. Thus, a meta-analysis was conducted to better understand the impact of lenalidomide maintenance in this setting. Patients and Methods The meta-analysis was conducted using primary-source patient-level data and documentation from three RCTs (Cancer and Leukemia Group B 100104, Gruppo Italiano Malattie Ematologiche dell'Adulto RV-MM-PI-209, and Intergroupe Francophone du Myélome 2005-02) that met the following prespecified inclusion criteria: an RCT in patients with NDMM receiving ASCT followed by lenalidomide maintenance versus placebo or observation with patient-level data available and achieved database lock for primary efficacy analysis. Results Overall, 1,208 patients were included in the meta-analysis (605 patients in the lenalidomide maintenance group and 603 in the placebo or observation group). The median PFS was 52.8 months for the lenalidomide group and 23.5 months for the placebo or observation group (hazard ratio, 0.48; 95% CI, 0.41 to 0.55). At a median follow-up time of 79.5 months for all surviving patients, the median OS had not been reached for the lenalidomide maintenance group, whereas it was 86.0 months for the placebo or observation group (hazard ratio, 0.75; 95% CI, 0.63 to 0.90; P = .001). The cumulative incidence rate of a second primary malignancy before disease progression was higher with lenalidomide maintenance versus placebo or observation, whereas the cumulative incidence rates of progression, death, or death as a result of myeloma were all higher with placebo or observation versus lenalidomide maintenance. Conclusion This meta-analysis demonstrates a significant OS benefit and confirms the PFS benefit with lenalidomide maintenance after ASCT in patients with NDMM when compared with placebo or observation.